The Promises and Realities of Integration in Synthetic Biology: A View From Social Science - Carter, Lucy; Mankad, Aditi (Frontiers in Bioengineering and Biotechnology, 2021)
Discussions about the responsible advancement of synthetic biology science are at fever pitch. Commentators from across the globe are calling for greater integrated science investments and more inclusive governance processes in the development and implementation of these potentially disruptive technologies. We take stock of the promises and realities of science integration by sharing our experiences of embarking on this very challenge in Australia. We conclude by offering suggestions for bringing about the enabling conditions for improved integration across the natural and social sciences.